1998
DOI: 10.1097/00006982-199818020-00007
|View full text |Cite
|
Sign up to set email alerts
|

Transplant of Full-Thickness Embryonic Rabbit Retina Using Pars Plana Vitrectomy

Abstract: Our procedure makes it possible to transplant embryonic retina to the appropriate position adjacent to the host retinal pigment epithelium, keeping the transplant architecture intact. The transplants show good layering and well-developed photoreceptors abutting the retinal pigment epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 0 publications
2
38
0
2
Order By: Relevance
“…The relatively atraumatic delivery technique with a very slow injection rate may also be an important factor in the good morphology observed in many of the grafts. Certainly, numerous previous studies of transplantation of intact fetal retinal sheets has demonstrated that minimization of surgical trauma is a critical factor in the achievement of laminated transplants and reducing rosette formation (Aramant et al, 1999;Ghosh et al, 1998). In our study, no rosettes were observed following subretinal transplantation of RPCs.…”
Section: Discussionsupporting
confidence: 42%
“…The relatively atraumatic delivery technique with a very slow injection rate may also be an important factor in the good morphology observed in many of the grafts. Certainly, numerous previous studies of transplantation of intact fetal retinal sheets has demonstrated that minimization of surgical trauma is a critical factor in the achievement of laminated transplants and reducing rosette formation (Aramant et al, 1999;Ghosh et al, 1998). In our study, no rosettes were observed following subretinal transplantation of RPCs.…”
Section: Discussionsupporting
confidence: 42%
“…This phenomenon, indicating abnormal growth of the graft along the scleral-vitreal axis, has not been found in eyes transplanted with neonatal or adult donor tissue [16,31], but has been noted in short-term fetal rabbit grafts [11]. Evidently, the confined space in the subretinal space does not allow lateral expansion of the graft, which would be more desirable.…”
Section: Graft-host Integrationmentioning
confidence: 96%
“…Since then, many investigators have reported encouraging results in this difficult field in animal models (Silverman and Hughes, 1989;del Cerro et al, 1991;Silverman et al, 1992;Gouras et al, 1994;Ghosh et al, 1998;Seiler and Aramant, 1998;Aramant et al, 1999;Kwan et al, 1999;Gouras and Tanabe, 2003) and in human patients (Das et al, 1999;Radtke et al, 1999;del Cerro et al, 2000;Humayun et al, 2000;Radtke et al, 2002;Radtke et al, 2004). Several studies have suggested some improvement in visual function as judged from light reflexes, behavioral testing, and electrophysiological responses in blind animal models (del Cerro et al, 1991;Silverman et al, 1992;del Cerro et al, 1995;Kwan et al, 1999;Radner et al, 2001;Woch et al, 2001;Sagdullaev et al, 2003;Thomas et al, 2004).…”
mentioning
confidence: 99%